Preparation of quaternary ammonium-modified silica and its adsorption of vanadium(V) - ZHANG Cuihong; WANG Jing; WANG Jie; YUAN Wenjiao (Gongye shui chuli)
Vanadium(Ⅴ) is an emerging contaminant reported in wastewater along with the increasing of alloy manufacturing, chemicals, new energy fields as a significant national strategy resource. In this study, a quaternary ammonium modified silica(SiO2@DMOA) material was synthesized for the adsorption of vanadium(Ⅴ) in aqueous solution. The results of TGA, FT-IR, SEM, and EDS confirmed the successful synthesis of SiO2@DMOA composite. Under the conditions of solution volume of 20 mL, vanadium(Ⅴ) concentration of 2 mmol/L, solution pH of 3.3, contact time of 15 minutes, and temperature of 298 K, the adsorption capacity for vanadium(Ⅴ) by SiO2@DMOA was 38.97 mg/g. The pseudo-second-order reaction kinetics and Langmuir adsorption isotherm model indicated that the process of adsorbing vanadium(Ⅴ) by SiO2@DMOA was a surface monolayer chemical adsorption process, and the intra-particle diffusion model and Boyd model demonstrated that liquid film diffusion was the main limiting rate of this adsorption process. Thermodynamic studies demonstrated the feasibility and spontaneity of vanadium(Ⅴ) adsorption by SiO2@DMOA, with ΔH0>0, ΔS0>0 and ΔG0<0. The influence of ionic strength (NaCl) on adsorption was found to be negligible at concentrations of less than 0.1 mol/L. Furthermore, within pH range of 3-5, the maximum separation factor(βV/Cr) between vanadium(Ⅴ) and chromium(Ⅵ) was 135.42. The adsorption efficiency of SiO2@DMOA did not show any significant attenuation after five cycles of adsorption-desorption experiments.